Steady state and thermoelastic analysis of a functionally graded rotating disk - Shahzamanian, M.M.; Sahari, B.B.; Bayat, M.; Mustapha, F.; Ismarrubie, Z.N.; Shahrjerdi, A. (2010)
In this paper, the steady state and thermoelastic analysis of a hollow functionally graded (FG) axisymmetric rotating disk is carried out. The inner and outer surfaces of FG disks are considered metal and ceramic respectively. The material properties of FG disk are assumed to be represented by a power-law distribution along the radial direction. Temperature distributions of FG disk are obtained by three methods, namely, using ANSYS parametric design language (APDL), developed finite element program and analytical solution. Thermal stress and thermal strain of FG disk are given by developed finite element program. The results show that the same temperature distributions are obtained